Swearing-In Ceremony of New Attorneys Held in Exhibit Hall - Watkins, Howard::::::::: (1981)
Presiding Justice of the Court of Appeal George Brown, State Bar District Five Board of Governor Robert Coyle, and U.S. District Court Judge M. D. Crocker